The birth of Russian intelligentsia from the spirit of the enlightenment: Alexander Radishchev - Subotić Milan (Filozofija i Društvo, 2009)
This text is the second part of a study about Alexander Radishchev, one of the leading representatives of Enlightenment in Russia's XVIII Century. Starting with explanation of the 'enlightened absolutism' of Catherine the Great, the author analyses the political and social ideas presented in Radishchev's book Journey from St. Petersburg to Moscow. Considering Radishchev as a 'father of Russian intelligentsia', the author stress that Radishchev's social criticism anticipated the later phenomenon of 'dissidence'.